English Education Students’ Engagement on Narrative Text Lexical Density Analysis through Project-Based Learning - Sanggam Siahaan; Siska Anggita Situmeang; Basar Lolo Siahaan (Ilomata International Journal of Social Science, 2026)
This research explores the use of lexical density of narrative texts in the context of Project-Based Learning. It applies a qualitative research method with a case study investigating 13 English Education Study Program students in three groups in learning the use of lexical density of narrative texts found in three online English textbooks published by the Government for 10th-12th grade students in Indonesia. The technique of the data analysis it uses is three interactive activities of the qualitative researcher, i.e., data collection/reduction, data display, and conclusion draw/verification. The results show that in the context of PBL, the lexical densities of three texts the students could invent are moderate, i.e., 4.45 or 55.64% in text-1, 3.15 or 52.12% in text-2, and 3.89 or 55.69% in text-3. In the classroom setting, the students could construct knowledge on the use of lexical density in narrative texts found in the online English textbooks for 10th-12th grade students in Indonesia. Since this research was a qualitative method with a case study design in the investigation on how a small number of research subjects analysed the use of lexical density of a small number of narrative texts in a classroom reality, it is suggested to apply other research type to investigate the use of lexical density in the narrative texts found in online English textbooks to shed reliable and indispensible pedagogical light to improve the capacity of the prospective English language teacher to face the communicative challenges in the 21st century.